The Paradox Of Illegal Parking Management: Dual Roles Of OMS In Rule Enforcement And Economic Exploitation And Their Implications For Urban Governance In Jakarta - Feriandy Feriandy; Munir Azhari; Wiwit Damayanti; Nurwulan Kusuma Devi; Haspul Naser (UNIVED Press, 2026)
This study aims to examine the dual role of community organizations (OMS) in managing illegal parking in Jakarta. The focus is to understand how OMS are not only involved in economic exploitation but also contribute to law enforcement in public spaces. A mixed-method approach is used to gain a comprehensive understanding of this phenomenon. Quantitative data was collected through surveys administered to users of illegal parking services and members of civil society organizations (CSOs). Qualitative data were collected through focused group discussions involving Pemuda Pancasila, FBR, Forkabi, and other informal actors. Findings show that CSOs have a dual function: they act as parking enforcement officers while also engaging in the collection of illegal fees. Although operating outside the formal legal framework, their presence reflects a hybrid governance model that fills institutional gaps in the provision of public services. More inclusive and participatory urban governance policies are needed to address the complexity of informal regulation in city management. This study contributes to the understanding of informal governance and hybrid authority in urban environments. The novelty lies in the dual role of OMS in addressing illegal parking and informal parking governance.